Treatment of mice with human recombinant interleukin-2 augments resistance to the facultative intracellular pathogen Listeria monocytogenes. - Haak-Frendscho, M (1989)
The effects of exogenously administered human recombinant IL-2 (hrIL-2) on resistance to Listeria monocytogenes infection were examined. Intravenous injection of hrIL-2 significantly enhanced antibacterial resistance in both BDF1 and C3H/HeJ mice. The beneficial effect of hrIL-2 was observed with as little as 0.6 micrograms per mouse, whereas optimum protection occurred at 6 micrograms per mouse, hrIL-2 was equally protective when administered concomitant with the listeriae or up to 24 h prior to infection; it had little effect if given after the bacterial challenge. Kinetic experiments indicated that both the peak bacterial burden and the time lag before L. monocytogenes began to be cleared from the spleen and liver were reduced in hrIL-2-treated mice as compared with control mice. Histopathological examination of spleens and livers confirmed that hrIL-2-treated Listeria-infected mice experienced considerably less damage to these organs than did control mice. Spleen cells from Listeria-infected mice exhibited depressed levels of mitogen-induced proliferation coincident with the peak bacterial burden in the spleen and liver and during the subsequent recovery from the infection. Administration of hrIL-2 to uninfected mice had no effect on spleen cell proliferation in response to mitogens in vitro, nor did hrIL-2 treatment restore normal levels of splenocyte proliferative responses to Listeria-infected mice. In addition, hrIL-2 treatment resulted in attenuated levels of serum colony-stimulating activity in infected mice as compared with control infected mice. Coadministration of both hrIL-2 and human recombinant interleukin-1 alpha at various dose and time combinations had no detectable additive or synergistic effect. Although these data do not suggest an obvious mechanism of action, they clearly demonstrate that hrIL-2 can augment host defense against the facultative intracellular pathogen L. monocytogenes.